Variability of leaf growth characteristics in the canopy of sessile oak and Austrian oak - Koncz, Péter (Acta Biologica Szegediensis, 2005)
In this study the variability of leaf growth traits was investigated within the canopy of the two dominant tree species of Quercetum petraeae-cerris forest community, covering 30% of the present forested area in Hungary. The investigation were performed in the "Sikfőkut Project" LTER site (Jakucs 1985). We compared the present leaf growth traits of species with those reported by Virágh (1985) for years of 1973-1975 before the decline of sessile oak in the site. After bud break leaves of the two canopy layers exhibited different rate in the increase of leaf area (La) and leaf mass (Lm). In spring shade leaves showed more intense increase in leaf area than in leaf mass. This resulted in a transitional large reduction of SLM in the shade leaves. In case of sessile oak the full leaf size was achieved within the same period in 2003 and 2004 but the area of mature leaves were larger in both canopy layers in 2004 than in 2003. In case of sessile oak the area of mature leaves in growing seasons of 2003 and 2004 increased significantly as compared to the period before the forest decline (Virágh 1985). In the upper canopy layer of Austrian oak the leaf area and leaf mass did not differ significantly from those reported for the period before the forest decline. In the lower layer of the canopy, however, the increase of leaf area was observed but the leaf mass exhibited similar values. In 2004 the loss of leaf area in the sun layer was 17% and in the shade layer 6 % as a consequnce of photophagous damages. In case of Austrian oak the loss of leaf area was smaller and amounted only to 1-5%.